Chemical Exchange Saturation Transfer MR Imaging is Superior to Diffusion-Tensor Imaging in the Diagnosis and Severity Evaluation of Parkinson’s Disease: A Study on Substantia Nigra and Striatum - Li, Chunmei; Wang, Rui; Chen, Haibo; Su, Wen; Li, Shuhua; Zhao, Xuna; Zhou, Jinyuan; Qiao, Jian; Lou, Baohui; Song, Guodong; Chen, Min (Frontiers in Aging Neuroscience, 2015)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by nigrostriatal cell loss. To date the diagnosis of PD is still based primarily on the clinical manifestations which may be typical and obvious only in advanced-stage PD. Thus, it is crucial to find a reliable marker for the diagnosis of PD. We conducted this study to assess the diagnostic efficiency of chemical-exchange-saturation-transfer (CEST) imaging and diffusion-tensor imaging (DTI) in PD at 3 Tesla by evaluating changes on substantia nigra and striatum. Twenty-three PD patients and twenty-three age-matched normal controls were recruited. All patients and controls were imaged on a 3 Tesla MR system, using an 8-channel head coil. CEST imaging was acquired in two transverse slices of the head, including substantia nigra and striatum. The magnetization-transfer-ratio asymmetry at 3.5 ppm, MTRasym(3.5ppm), and the total CEST signal intensity between 0 and 4 ppm were calculated. Multi-slice DTI was acquired for all the patients and normal controls. Quantitative analysis was performed on the substantia nigra, globus pallidus, putamen and caudate. The MTRasym(3.5ppm) value, the total CEST signal intensity and fractional anisotropy (FA) value of the substantia nigra were all significantly lower in PD patients than in normal controls (P = 0.003, P = 0.004 and P < 0.001, respectively). The MTRasym(3.5ppm) values of the putamen and the caudate were significantly higher in PD patients than in normal controls (P = 0.010 and P = 0.009, respectively). There were no significant differences for the mean diffusivity (MD) in these four regions between PD patients and normal controls. In conclusion, CEST MR imaging provided multiple CEST image contrasts in the substantia nigra and the striatum in PD and may be superior to DTI in the diagnosis of PD.